SENAM AEROBIK LOW IMPACT TERHADAP DISMENORE PRIMER PADA REMAJA PUTRI DI SMKN 1 MARTAPURA - Pertiwi, Melinda Restu; Wahid, Abdurahman; Marlinda, Evy (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
Primary dysmenorrhea is menstruation pain experienced by female adolescents which comes fromuterus cramp. This is caused by the uterus contraction and the detached uterus wall because of theincreasing of prostaglandin. Dysmenorrhea caused 14% of female students absence at school and notparticipating in school routines. To overcome this, non-pharmacology therapy is needed in order toavoid the side effect on their body. This study was aimed to find the effect of low impact aerobicexercise on female students. This study was pre-experimental with one group pretest-posttest design.The scale of pain was measured using Numeric Rating Scale (NRS). The sample gathering was doneby purposive sampling of 22 respondents at SMKN 1 Martapura. The data analysis used Wilcoxontest with the significance of 95%. The results of the statistical test p<α was 0,000<0,05 which meansH0 was denied and Ha was accepted. It could be concluded that there was an effect of low impactaerobic exercise to reduce the scale of menstruation pain on female students.